The shamanic themes in Chechen folktales - Berman, Michael, 1951- (Newcastle, UK : Cambridge Scholars, 2008)
ÂAll intellectuals driven by nationalist sentiments directly or indirectly are always preoccupied with searching for the most ancient roots of their budding nations in order to ground their compatriots in particular soil and to make them more indigenous.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 650
Keywords: Shamanism -- Russia (Federation); Tales -- Russia (Federation) -- x; SOCIAL SCIENCE -- Folklore & Mythology; Shamanism; Tales; Russia (Federation) -- 2; Electronic books; Criticism, interpretation, etc